P342 Lactobacillus rhamnosus protection against Candida-induced vaginal epithelial cell damage is Candida albicans strain-dependent. (20th September 2022) - Valentine, Marisa; Alonso-Román, Raquel; Abdul-Rahman, Shameema; Bougnoux, Marie-Elisabeth; d'Enfert, Christophe; Hube, Bernhard; Gresnigt, Mark S
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM Microbial dysbiosis can lead to vulvovaginal candidiasis (VVC) which is characterized by a pathogenicity-induced inflammatory response progressing to neutrophil-driven immunopathology. Probiotic treatment has varied success rates and some women still experience VVC despite being colonized by lactobacilli. It is, therefore, imperative to identify factors that influence the success of probiotic treatment for VV C. We aimed to evaluate how Candida albicans strain differences contribute to the varying degrees to which probiotics such as Lactobacillus rhamnosus protect against Candida -induced epithelial tissue damage. We screened the commonly used highly virulent C. albicans laboratory strain SC5314, 24 C. albicans strains from different clades, and several vaginal C. albicans isolates. L. rhamnosus was used to colonize vaginal epithelial cells prior to C. albicans infection and vaginal epithelial cell damage was measured. Compared to SC5314, most C. albicans strains induced relatively low or no epithelial cell damage. Even increased multiplicities of infection did not increase epithelial damage to the level of SC5314. Three groups were identified based on the effect of L. rhamnosus on Candida -induced epithelial cell damage. Bacterial colonization decreased, did not affect, or even increased tissue damage during infection. The different C. albicans clades showed no correlation with the protective phenotypes. However, increased epithelial tissue damage in the presence of lactobacilli was generally observed with strains that alone were unable to damage the epithelium. Some strains had an enhanced potential to grow at low pH, yet growth at low pH alone was not able to distinguish the three groups. The protective potential of L. rhamnosus is highly C. albicans strain-dependent. Our data hint toward a potential multifactorial effect involving stress-resistance and metabolic interplay. Elucidating the processes that lead to epithelial protection or enhanced damage will be crucial to predict whether probiotic lactobacilli may be beneficial or detrimental for a patient and may help to design generally protective probiotics.